Antibacterial Activity of Leaves and Fruit of Pistacia lentiscus - Dabnoun, Fatimah M. Omar; Mahjoub, Wafaa S. Ali; Youssif, Haneia A. Jebril; Alteerah, Munay A. (International Journal of Scientific Research in Biological Sciences, 2022)
The study was carried out on the ethanolic and aqueous extracts of the Pistacia lentiscus leaves and fruits. The extracts were tested for its antibacterial activity against the following organisms; Staphylococcus aureus, Esherichia coli and Klebsilla pneumonia at different concentrations of 40, 80, 100, 120 ?l. The ethanol extract of Pistacia was more effective than water extract. ethanol extract showed variation in the anti-bacterial activity toward S. aureus that isolated from clinical source, the zone of their inhibition ranged between (10-25mm).